MISINTERPRETATION OF SALAFI JIHADIST ON JIHĀD VERSES: AN ANALYSIS - Hudzaifah Achmad Qotadah; Maisyatusy Syarifah; Adang Darmawan Achmad (Asy-Syari'ah, 2021)
Nowadays, the term "Jiha̅d" has taken on the connotation of a frightening term (logophobia). This is due to the fact that religious extremists use it in a very narrow context. Unfortunately, the concept of pure and vast Jihad has been tainted by insights and actions that have transcended its borders, resulting in the term Jihad being viewed negatively by some segments of the world's society. The study examines how these scholars (of Salafi Jihadism) interpret these specific verses of the Holy Quran, as well as how their concepts and explanations regarding Jihad verses differ from other scholars. A thorough qualitative method is used in this article to examine the misinterpretation of the Jiha̅d verses used by Salafi Jihadism. The study shows, first, the Salafi-Jihadi movement interprets jihad verses only based on literal meanings, ignoring the context of the asbab nuzul verses, pay less attention to the period and socio-historical verses revealed. Second, considering jihad as a physical struggle only and war in the way of Allah as a natural obligation for Muslims.